Māori perspectives on the science and innovation system - Harmsworth, Garth (New Zealand Science Review, 2011)
​Enormous opportunities exist for Māori to be actively involved in the New Zealand science, research, and innovation system both in terms of what Māori can offer the system, and in terms of what the system has to offer Māori. The current system in New Zealand indicates a passive Māori involvement – low participation rates, low educational attainment rates in science, engineering, and technology, and low rates of engagement between the research, science, technology (RS&T) and innovation sector and Māori organisations and enterprises. There are signs that this is starting to change, and there are small islands of success, but these are limited and Māori remain greatly under-represented in the sector. At the same time, there is an emerging and strengthening Māori economy that is becoming increasingly reliant on science and innovation to realise opportunities – for growth, productivity improvements, competitive advantage, and environmental sustainability. All of this is needed to meet aspirational goals (Harmsworth et al. 2002; Durie 2003, 2005) such as higher standards of living, education, health, economic development, prosperity, enterprise, social justice, and equity, as well as strengthen cultural distinctiveness. The current situation provides huge potential for Māori to be engaged and contribute to the RS&T system as a whole. However, to capitalise on Māori participation and input into the New Zealand science and innovation system, a number of key elements and dimensions, pivotal to growing and sustaining the New Zealand and Māori economies, need to be addressed concurrently.